2007
DOI: 10.1007/s00259-007-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole body [11C]-dihydrotetrabenazine imaging of baboons: biodistribution and human radiation dosimetry estimates

Abstract: The largest radiation dose from [(11)C]-DTBZ is to the stomach wall. This dose estimate, as well as the radiation dose to other radiosensitive organs, must be considered in evaluating the risks of multiple administrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…For instance, the most promising beta cell marker, VMAT2, is produced in beta cells and monoaminergic neurons [10] but recent studies indicate that VMAT2 is also present in other islet cells besides beta cells [13]. Promising preliminary data were obtained with 11 C-labelled dihydrotetrabenazine (the PET ligand binding specifically to VMAT2) in streptozotocin (STZ)-induced diabetic Lewis rats [11] and in the BB-DP rat [12], but the data obtained in baboons [15] and in patients with longstanding type 1 diabetes [16] are not conclusive. A recent study using an 18 F-labelled epoxide derivative of tetrabenazine showed good pancreas specificity and significantly reduced uptake in rat liver [9], but it remains unclear whether substituting isotopes will produce better biodistribution results in larger mammals.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…For instance, the most promising beta cell marker, VMAT2, is produced in beta cells and monoaminergic neurons [10] but recent studies indicate that VMAT2 is also present in other islet cells besides beta cells [13]. Promising preliminary data were obtained with 11 C-labelled dihydrotetrabenazine (the PET ligand binding specifically to VMAT2) in streptozotocin (STZ)-induced diabetic Lewis rats [11] and in the BB-DP rat [12], but the data obtained in baboons [15] and in patients with longstanding type 1 diabetes [16] are not conclusive. A recent study using an 18 F-labelled epoxide derivative of tetrabenazine showed good pancreas specificity and significantly reduced uptake in rat liver [9], but it remains unclear whether substituting isotopes will produce better biodistribution results in larger mammals.…”
Section: Introductionmentioning
confidence: 92%
“…2f and data not shown). To gain information on the presence of FXYD2γa during human pancreas development, samples from fetal human pancreas (15,18,19,24 and 25 weeks of gestation) were analysed by triple immunofluorescence labelling (Fig. 5).…”
Section: Mpssmentioning
confidence: 99%
See 1 more Smart Citation
“…PET studies of VMAT2 pathophysiology are in their infancy; however, several important studies have been published by the group at Columbia University (19)(20)(21). In an investigation (19) with 11 C-DTBZ, they demonstrated decreased radioligand uptake in the pancreas of Lewis rats with streptozotocin-induced diabetes, compared with euglycemic historical controls.…”
mentioning
confidence: 99%
“…These studies further supported the notion that PET-based quantitation of VMAT2 provides a noninvasive measurement of BCM that may be useful for studying the pathogenesis of diabetes and monitoring therapeutic interventions. In a PET study of 11 C-DTBZ in baboons (21), these investigators demonstrated that most of the injected tracer localized to liver and lungs, followed by the intestines, brain, and kidneys. The highest estimated absorbed radiation dose was in the stomach wall, and the dosimetry of doses proposed for human imaging was determined to be safe.…”
mentioning
confidence: 99%